Pengembangan Kawasan Andalan Provinsi Kalimantan Selatan - Yusuf Asyahri; Syafril Syafril (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2018)
Economic disparity between regions is a common aspect in the economic activities of a region. This inequality is basically caused by differences in natural resource content and differences in demographic conditions in each region. The inequality is then the reason for the birth of Regional Regulation of South Kalimantan No. 9 of 2000 on South Kalimantan Spatial Planning. Therefore, this study is an economic study to see and compare the economic potentials of the mainstay of South Kalimantan Province as well as whether or not the Regulation No. 9 of 2000 is correct. Research Methods are quantitative descriptive. Data collection techniques used literature study and analytical techniques using LQ, Regional Typology, Williamson Index and Theil Entropy. The result of the analysis shows that the inappropriate area becomes the mainstay area with regional typology analysis only Hulu Sungai Utara (HSU), Hulu Sungai Selatan (HSS), Banjar Regency, and Balangan Regency. Because these areas are included in Quadrant III. Economic disparities in the areas of Kandangan and Mainstay area can not be determined as a reliable area. Therefore, the division of the Mainstay Area as in the Regulation of Kalimantan Seelatan No 9 of 2000 on South Kalimantan Spatial Plan needs to be reviewed.